Pengajaran Persiapan Ujian Nasional Mata Pelajaran Matematika di SMP Negeri 37 Samarinda - Ganjar Susilo; Nur Aisyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2020)
Community Service conducted at SMP 37 is teaching national math preparation tests for class IX. The method of community service in Samarinda 37 State Junior High School is by teaching using the junior high school national exam practice module. Activities carried out through the stage of providing material operations of fractions, value comparisons and reversals of values, ranks and roots, calculation of loan and savings interest rates, arithmetic sequences and sequences and geometry, linear and quadratic equations, sets, linear functions, line equations, line gradients, flat circumference and shape area, congruent and congruent triangles, circle angle, circle circumference, circle elements, prism and pyramid elements, volume and surface area of ​​prism and pyramid, statistics, sample space, and opportunity. After all the material has been submitted, it is continued with the prediction of the national mathematics exams in 2013, 2014, 2015, 2016, 2017, and 2018 with the development of the developed training modules. From the results of community service in Samarinda 37 Public Middle School, the level of student satisfaction found using modules was 41.52% very satisfied, 57.40% satisfied, 1.07% quite satisfied, and 0.00% dissatisfied. On the other hand, students also find it easier to understand learning if the teacher uses modules as teaching material in class